Effect of copper sulphate on Cryptocaryon irritans based on metabolome analysis - Quanjun Zhan; Liang Miao; Jing Zhao; Haojie Hu; Hao Cui; Shan Jin; Jiasong Xie; Dong Qian; Rongrong Ma (Journal of Fish Diseases, 2023)
Cryptocaryon irritans is one of the most harmful marine parasites in mariculture. Copper sulphate is often used to kill parasites and the influence of copper sulphate on the tomont stage of C. irritans was explored in this study. The results showed that excystment rate was not significantly affected when tomonts were exposed to 5 mg/L (76.7%) and 10 mg/L (78.9%) of copper sulphate for 3 h. However, excystment rate was significantly inhibited when exposed to 15 mg/L (33.3%) for 3 h and 5 mg/L (28.9%), 10 mg/L (33.3%) and 15 mg/L (33.3%) for 6 h. After treatment with high concentrations of copper sulphate, the interior of the tomonts was fuzzy under the microscope, and the division process could not be observed. Metabolomic results combined with preliminary transcriptome analysis results showed that the tomonts were induced to produce linoleate, riboflavin, inositol and other substances under the stress of Cu 2+ , which affected the antioxidant mechanism of the body. Using MDA content determination and antioxidant enzyme activity analysis, copper sulphate was found to cause oxidative damage to tomonts by affecting the generation of metabolites, leading to the death of tomonts.

Poly(lactic-co-glycolide) polymer constructs cross-linked with human BMP-6 and VEGF protein significantly enhance rat mandible defect repair - Anusuya Das; Brian A. Fishero; J. Jared Christophel; Ching-Ju Li; Nikita Kohli; Yong Lin; Abhijit S. Dighe; Quanjun Cui (Cell and Tissue Research, 2016)

Inhibition of differentiation and function of osteoclasts by dimethyl sulfoxide (DMSO) - Chunxi Yang; Vedavathi Madhu; Candace Thomas; Xinlin Yang; Xeujun Du; Abhijit S Dighe; Quanjun Cui (Cell and Tissue Research, 2015)

Local delivery of FTY720 accelerates cranial allograft incorporation and bone formation - Cynthia Huang; Anusuya Das; Daniel Barker; Sunil Tholpady; Tiffany Wang; Quanjun Cui; Roy Ogle; Edward Botchwey (Cell and Tissue Research, 2012)